Hukum Wudu Bagi Pengguna Kosmetik Waterproof Dalam Perspektif MUI Langkat - Muhammad Syarifan (Journal Smart Law, 2025)
The use of waterproof cosmetics among Muslim women is increasing along with the development of modern lifestyles. However, this type of cosmetic raises fiqh problems, especially related to the validity of ablution, because of its properties that can block the arrival of water to the skin. Wudu is a valid condition for prayer, so the existence of a barrier (ḥājib) on ablution members has direct implications for the validity of worship or not. This study aims to: (1) examine the views of Islamic jurisprudence regarding the legal requirements of ablution related to the existence of obstacles in ablution members, (2) analyze the views of the Indonesian Ulema Council (MUI) of Langkat Regency on the law of ablution for users of waterproof cosmetics, and (3) identify practical solutions offered by MUI Langkat for Muslim women who use waterproof cosmetics. This study employed a qualitative approach with a normative-empirical approach to Islamic law. Data were obtained through interviews with the Indonesian Ulema Council (MUI) officials in Langkat Regency, serving as the primary data source. The data were then analyzed using the Miles and Huberman analysis model, which encompasses three main stages: data reduction, data presentation, conclusion drawing and verification, while still considering both the Islamic jurisprudence (fikih) and socio-religious approaches. The results of the study show that according to Islamic jurisprudence, one of the valid conditions for ablution is the arrival of water to the skin without any obstruction. Waterproof cosmetics that form a waterproof layer are included in the category of ḥājib which can cause ablution to be invalid if not removed. The MUI of Langkat Regency is of the view that the use of waterproof cosmetics is basically allowed, but it must be removed first before performing ablution so that the water can hit the skin perfectly. The solutions offered by MUI Langkat include removing cosmetics before ablution, ablution before using cosmetics, and using alternative cosmetics that do not block water. This research is expected to be a practical guideline for Muslim women in maintaining the validity of ablution and prayer in accordance with the guidance of Islamic law.